Advanced Mathematical Techniques in Science and Engineering. - Ram, Mangey; Davim, J. Paulo (River Publishers series in management sciences and engineering., 2018)
In recent years, mathematical techniques applied to novel disciplines within the science and engineering have experienced extraordinary growth. Advanced Mathematical Techniques in Science and Engineering focusses on a detailed range of mathematics applied within various fields of science and engineering for different tasks. Topics of focus include:- Analysis of Consensus-Building Time in Social Groups- Modeling of intersystem accidents in critical infrastructure systems- Stochastic approaches to analysis and modeling of multi-sources and big data- Performance evaluation of computational DoS attack on access point in Wireless LANs- Ranking methods for decision-making under uncertainty- Understanding time delay based Modeling & Diffusion of technological products- Role of soft computing in science and engineering- Complex system reliability analysis and optimization- Tree growth models in forest ecosystems modellingThis research book can be used as a reference for students in a final year undergraduate engineering course, such as mechanical, mechatronics, industrial, computer science, information technology, etc. Furthermore, the book can serve as a valuable reference for academics, engineers and researchers in these and related subject areas.